Language and Reading Disorders in Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
The severity and range of linguistic impairments in youths with epilepsy were studied at UCLA, Los Angeles, State Fullerton University, and UC at Irvine, California.